Democrats and dissenters - Guha, Ramachandra (Penguin books, 2016)
A major new collection of essays by Ramachandra Guha, Democrats and Dissenters is a work of rigorous scholarship on topics of compelling contemporary interest, written with elegance and wit. The book covers a wide range of themes: from the varying national projects of India's neighbours to political debates within India itself, from the responsibilities of writers to the complex relationship between democracy and violence. It has essays critically assessing the work of Amartya Sen and Eric Hobsbawm, essays on the tragic predicament of tribals in India -- who are, as Guha demonstrates, far worse off than Dalits or Muslims, yet get a fraction of the attention -- and on the peculiar absence of a tradition of conservative intellectuals in India. Each essay takes up an important topic or an influential intellectual, as a window to explore major political and cultural debates in India and the world. Democrats and Dissenters is a book that is certain to be widely read and even more widely discussed.--